Tradisi Adu Kabau di Nagari Batu Palano dalam Karya Seni Grafis - Yofita Sandra, S.Pd., M.Pd., Rahman Surya, Dr. Budiwirman, M.Pd., (Serupa The Journal of Art Education, 2018)
The purpose of this final work is to visualize and preserve Minangkabau culturein West Sumatra into Serigraphy Graphic artwork. The Adu Kabau traditionhasbeen beginningto disappear in 1997 in West Sumatra because someunscrupulous people are notresponsible for gambling openly against the IslamicShari'a. Tradition Adu Kabau inMinangkabau is a buffalo that fights matchconducted for several traditional events suchas appointment of Nagari and alekNagari guardians through various processions of implementation. The theme ofthis work is Adu Kabau Tradition in Nagari Batu Palano in Graphic Arts.The method of creating this final paper uses five stages: preparation stage,elaboration stage, synthesis stage, concept realization stage,completion stageandexhibition of Graphic art work. Technique used is technique of Serigraphy.These tengraphic works revisited the procession of the Adu Kabau Traditionwhich is gettingdisappearing in West Sumatra due to the negative influence of the irresponsible parties.The tenth title of the work is: 1) Go away, 2) Preparation 3) Fighting 4). Mambajak 5)Struggle 6)Courage 7)Preparation # 2 8). Bound (9)Preparation # 110) Tame.Keywords: Tradition, Adu Kabau, and Serigraphy.